Improving Learning Outcomes of Accounting Materials for Service Companies Through Flipbook Maker-Assisted E-modules - Yuliyanto, Riyan; Pujiati, Pujiati; Suroto, Suroto; Rahmawati, Diya Rofika (Kayon Media, 2025)
The purpose of this study is to develop an e-module assisted by a flipbook maker on accounting materials for service companies that are valid and feasible to improve student learning outcomes. The subjects at the expert validation stage are expert lecturers and practitioners, while in the research trial are Class XII students of State High School (SMA) 1 Seputih Banyak ofÂ who are mostly majoring in Social Sciences. The method used in this study is research and development. The study results show that the e-module of accounting learning for service companies based on flipbook maker after being validated by experts and practitioners obtained an assessment with a total score percentage of 76%. Student assessment at the one-on-one test stage obtained a total score percentage of 91%. Therefore, this e-module is feasible and effective in improving student learning outcomes. The t-test tested the effectiveness of the e-module, a significance value of 0.003 0.05 which showed that the use of e-modules for learning accounting for service companies was effective in improving student learning outcomes.